Evaluación de estrategias de eficiencia energética para la empresa florícola “Sky Valley”, en el cantón Pedro Moncayo, período octubre 2021- marzo 2022. - Cumbal Andrango, Jeferson Alexander (2022)
The present study was carried out in the SKY VALLEY flower company, located in the Pedro Moncayo canton, dedicated to the cultivation and commercialization of roses nationally and internationally. The purpose of this project is to evaluate the energy efficiency strategies which include the analysis of energy quality in the electrical supply system, the determination of the dominant energy vector and the evaluation of the existing energy potential in the location of the company. This study has a bibliographic and field review, which contributed significantly to the development of the topic. Data on the electrical parameters of transformer two of the company were recorded with a FLUKE 435-11 network analyzer, in addition to this, the lifting of loads and the single-line diagram of the electrical system were carried out, the same data that was later used in the simulation carried out in the ETAP software, through which it was possible to analyze the significant disturbances that the system presents, such as low power factor and current harmonics. Likewise, with the history of wind speed, solar irradiation and stem waste that can be used as biomass, it was analyzed to find out if the demand of the floriculture company can be satisfied with the implementation of renewable energies, by defining the greatest potential. A simulation of the photovoltaic system is carried out in the PVsyst software and it was determined that the implementation is not viable due to the generation cost of 0.10 USD/kWh compared to the sale price of 0.065 USD/kW regulated by ARCERNNR-003/ 2021 therefore it is not possible to recover the investment. Finally, solutions are proposed to mitigate the existing disturbances in the system and the comparison with the proposed renewable energies, showing the feasibility and benefits that the project presents, both economic and technical.